2019
DOI: 10.4103/ijem.ijem_526_19
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D, thyroid autoimmunity and cancer: An interplay of different factors

Abstract: Background and Aims:In spite of large volume of data linking Vitamin D with cardiovascular morbidity, autoimmunity, cancer, and virtually every organ system, Vitamin D and thyroid is a lesser-known aspect of Vitamin D in clinical practice. This article intends to highlight the current literature on the impact of Vitamin D status and supplementation on thyroid autoimmunity and cancer.Methods:References for this review were identified through searches of PubMed for articles published to from 1950 to August 2019 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 72 publications
0
4
0
2
Order By: Relevance
“…Vitamin D enhances the innate immune response, exerts immunomodulatory properties and moderates cytokines via the VDR, resulting in thyroid damage and dysfunction. 24 At the first stage of thyroid damage, T3 and T4 are released into the serum, resulting in the development of hyperthyroidism. As the extent of thyroid damage, the production of T3 and T4 is inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D enhances the innate immune response, exerts immunomodulatory properties and moderates cytokines via the VDR, resulting in thyroid damage and dysfunction. 24 At the first stage of thyroid damage, T3 and T4 are released into the serum, resulting in the development of hyperthyroidism. As the extent of thyroid damage, the production of T3 and T4 is inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used therapy in the present study was the combination therapy of vildagliptin and metformin at 50/500 mg dose followed by vildagliptin monotherapy at 50 mg dose. Several real-world studies from India have reported the use of vildagliptin monotherapy (4%-18%) [25,26] and vildagliptin and metformin combination therapy (37%) [27] for the management of T2DM. About 70% of the present study cohort used the twice-daily formulation.…”
Section: Discussionmentioning
confidence: 99%
“…level of TSH following vitamin D de ciency was considered to stimulate the growth of thyroid cells, causing TNs and thyroid carcinoma [18]. In addition, with the vitamin D receptor and ossifying triol involved [29], vitamin D was related to the regulation of cell differentiation, apoptosis, and in ammation [30], all of which signi cantly contributed to the formation of TNs [31].…”
Section: Potential Mechanisms Of the Associationmentioning
confidence: 99%